IMPLEMENTASI KEBIJAKAN REVITALISASI DAN KONSERVASI BANGUNAN BERSEJARAH KAWASAN KOTA LAMA DI KOTA SEMARANG - Bhakti Sulistyo; Wiwik Widayati; Puji Astuti (Journal of Politic and Government Studies, 2013)
ABSTRACTIn this study, researchers wanted to know what are the policies revitalization andconservation of historic buildings in the old town area of the city of Semarang, and how itsimplementation, whether run smoothly or encounter obstacles or barriersThis type of research is a qualitative descriptive study using a type analitis.Penelitiananalyzing how the implementation of the policy of conservation and revitalization of theold cityAfter doing research on the sole discretion and analyze its implementation, the obtainedresults of research that says that in the sole discretion of Semarang city governmentestablished a body called the management board of the old city area, not only that, thegovernment also issued a grand design to handle the problems of the city lama.dan resultsstill less and not satisfactory, because a lot of the programs contained in the grand designis still a lot that has not been implemented and the results are not satisfactory.Advice that I can give Semarang city government should be more assertive in monitoringits implementation and provide strict sanctions for agencies or bodies which are lessserious in addressing this issue with the arrangement of the old city.Keywords: policy implementation, revitalization and conservation, the old city ofSemarang